EFEKTIVITAS VARIASI DOSIS FERRI KLORIDA (FeCl3) SEBAGAI KOAGULAN DALAM MENURUNKAN KADAR KADMIUM (Cd) PADA AIR LINDI TPA JATIBARANG SEMARANG - Devi Sarah Silaban; Sulistyani Sulistyani; Mursid Rahardjo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Leachate is the liquid waste that comes out of a pile of TPA containing heavy metals cadmium of 3.425 mg/l and beyond normal limits according to the Minister of Environment and Forestry Republic Indonesia Regulation Number 59 Year 2016 and the normal limit cadmium content in leachate is as much as 0.1 mg/l. Cadmium is highly toxic and can be harmful to the environment. Using Ferric chloride with coagulation-flocculation method is one technology that can be used to remove heavy metals in leachate. The purpose of this study was to determine the effectiveness of dose variation (7 grams, 12 grams and 17 grams) of ferric chloride as a coagulant in lowering levels of cadmium in TPA Jatibarang. This type of research was a true experiment with pretest and posttest with control group design. The populations in this study were all leachate in the inlet TPA Jatibarang Semarang. Data were analyzed by ANOVA (p value ≤ 0.05). The results showed the initial concentration of Cd of 0.862 mg/l and remained above the quality standard (0.1 mg/l). The average pH and temperature of the leachate before treatment was 7 and 26.48°C. After treatment with FeCl3 7 grams of 7 and 25.75°C, pH and temperature after treatment with FeCl3 12 grams by 7.16 and 25.58°C, pH and temperature after treatment with FeCl3 17 grams of 7 and 26°C. Decreased levels of Cd in 7 grams dose as much as 21.1%, 12 grams dose as much as 41.3% and 17 grams dose as much as 72.8% ANOVA showed p-value = 0.0001 or ≤ 0.05, which means that there were differences in the metal levels decrease Cd in leachate by using a treatment dose variation Ferric chloride. That was because ferric chloride was hydrolyzed to interact with and neutralize the negative colloids changes. It can be concluded that the administration of dose variation Ferric chloride effect on the levels of the metal cadmium (Cd) in landfill leachate water Jatibarang Semarang.